Pharmaceutical care practice in patients with chronic kidney disease - Dadier Antonio Arroyo Monterroza; José Francisco Castro BolivarPharmacist, Master in Pharmaceutical Care, Universidad de Granada, Spain (Farmacia Hospitalaria)
Introduction: The impact of chronic kidney disease in health is no longer just a patient-physician issue, not only in terms of the increase in the number of patients diagnosed, but also regarding the human and economic cost for health systems. That is why Pharmaceutical Care should include SOPs structured by criteria reached by consensus to conduct Pharmaceutical Care Practice, which will enable to prevent, identify and solve any negative outcomes in patients that are associated with medication. Objectives: To learn about the types of problems related to medications and negative outcomes associated with drugs that can be detected, prevented and solved in patients with chronic kidney disease, through pharmaceutical care practice. Method: A quasi-experimental study was conducted, with a descriptive and retrospective design, in 47 hospitalized patients diagnosed with chronic kidney disease in a high-complexity clinic. Using the DADER methodology, their pharmacological treatments were analyzed, and it was verified whether they were necessary, effective and safe, taking into account variables such as the negative outcomes associated with medication, medication-related problems, pharmaceutical interventions, and kidney failure stages. Results: Fifty-one (51) negative outcomes associated with medication were detected during the study; of these, 13.72% were for Necessity, 45.1% for Effectiveness and 41.18% for Safety. A total of 41 pharmaceutical interventions were conducted, 35 were accepted and 6 were not accepted. Of these 6 non-accepted interventions, 3 health problems were not solved, 12 dose re-adjustments were conducted, with cefepime as the drug with the highest number of dose adjustments; most patients were in Stage III and V of CKD, and its main cause was hypertension and Diabetes Mellitus II. Conclusion: The most prevalent NOMs were those for Non-Quantitative Insecurity, therefore these are a highly prevalent problem. This highlights the importance of this public health problem and its major clinical, social and economic impact, associated with Chronic Kidney Disease; therefore, it is necessary to involve all health professionals and patients, to obtain as a result a better use of medications, the prevention of NOMs and a reduction in morbidity associated with pharmacotherapy.